BS EN 60404-17 Ed.1.0. Magnetic materials. Part 17. Methods of measurement of the magnetostriction characteristics of grain oriented electrical steel strip and sheet by means of a single sheet tester and an optical sensor (2nd April 2020) - British Standards Institution,
No abstract available